Particle concentration levels of various nanofluids in plate heat exchanger for best performance - Tiwari A.K.; Ghosh P.; Sarkar J. (My University, 2025)
A heat exchange device using nanofluid needs to operate at best nanoparticle loading to get the maximum heat transfer performance. In this paper, an attempt has been made to optimize different nanofluid particle volume fractions based on a maximum heat transfer rate, convective heat transfer coefficient, overall heat transfer coefficient, effectiveness and performance index. The novelty of the present study is the optimization of particle volume fraction of various nanofluids based on experimentation in the commercial plate heat exchanger for wide range of nanoparticle volume fraction (0-3%). Effects of other operating conditions on the optimization have been discussed as well. Results show that for maximum enhancement of heat transfer characteristics, different nanofluids work at different optimum volume concentrations. For CeO2/water, Al2O3/water, TiO2/water and SiO2/water nanofluids, the optimum volume concentrations are 0.75%, 1%, 0.75% and 1.25%, respectively, at the flow rate of 3 lpm. The corresponding maximum heat transfer enhancements are about 35.9%, 26.3%, 24.1%, and 13.9%, respectively. Present study indicates that the optimum concentration for maximum performance index is lower than that for maximum heat transfer rate. Moreover the effect of nanomaterials is more predominant than that of heat transfer fluid temperature or volume flow rate. © 2015 Elsevier Ltd. All rights reserved.